Dampak Batik Nagori Terhadap Kemajuan Pariwisata Kuantan Singingi - Zahirah, Nabilah (Journal of Tourism Sciences, Technology and Industry, 2024)
This research explores the impact of Batik Nagori on the advancement of tourism in Kuantan Singingi. Batik Nagori, located in Pisang Berebus village, Gunung Toar subdistrict, Riau province, produces traditional batik motifs inspired by local culture and heritage. The study utilizes a qualitative approach with an ethnographic method, focusing on the role of Batik Nagori in enhancing the region's tourism sector. Findings indicate that the distinctive motifs of Batik Nagori, such as Perahu Beganduang and Jalur, contribute to promoting the local culture and attracting both domestic and international tourists. The involvement of the younger generation and government efforts in supporting batik as a cultural asset further strengthens the region's tourism potential. This research highlights how Batik Nagori not only preserves cultural heritage but also fosters economic growth through tourism, making it a significant cultural and tourism asset for Kuantan Singingi.